Freedom to Struggle: The Ironies of Colson Whitehead - Adam Kelly (Open Library of Humanities, 2018)
This essay explores the changing role played by the idea of freedom in the fiction of Colson Whitehead. I begin by outlining some of the significations of ‘freedom’ within American culture before and during the period of neoliberal hegemony, placing particular emphasis on trends in the word’s provenance for African Americans between the civil rights era and the time in which Whitehead is writing. I then undertake an extended comparison between Whitehead’s novels Apex Hides the Hurt (2006) and The Underground Railroad (2016). I argue that in Apex—published against the background of the Bush doctrine and the American wars in Iraq and Afghanistan—Whitehead treats freedom ironically. The novel both pursues and treats critically a postmodern aesthetics that envisages symbolic action on language as the primary ground of politics. The Underground Railroad, by contrast, inhabits an African American literary genre—the novel of slavery—that is strongly wedded to discourses of bondage and freedom. This novel, arriving a decade after Apex, shows Whitehead responding to changes in American society and culture—particularly the advent of Black Lives Matter and a growing public awareness of the implications of mass incarceration policies for African Americans—that seem to call for a more sincere reckoning with the notion of freedom. I conclude with a discussion of time in Whitehead, arguing that his distinctive engagement with temporality lies at the heart of the vision of freedom after neoliberalism offered by his fiction.